The Degree to Which Duolingo Can Improve The Fluency of One’s Foreign Language (Narrative Research) - Nurah Abdul Wahid Abdullah Siddik (Syntax Literate, 2022)
Learning a foreign language has become a very appealing and important ability in the contemporary world. The advantages of learning foreign languages are mushrooming as the world becomes increasingly globalized. This research explores the degree to which Duolingo can improve the fluency of one’s foreign language. The participant is the researcher herself as it uses narrative research (autobiography). The participant had taken the Diplôme d'études en langue française (DELF) – Level A1 test after using Duolingo for a month. This research explores the methodology the researcher used to improve the fluency of her French. The results suggest that Duolingo can improve the fluency of one’s foreign language to some extent that it helped the researcher pass the A1 level test by 83%. The skills being tested are listening comprehension, reading comprehension, writing production and speaking. Each of these skills is tested and graded respectively by the by France Education International (France Éducation international or FEI) for France's Ministry of Education. The researcher got 16/25 in the listening comprehension, 21/25 in the reading comprehension, 22/25 in the writing production, and 24.5/25 in speaking. Recommendations to extend the effectiveness of using Duolingo to improve the fluency of one’s foreign language is discussed further in the research. In general, it is suggested that the learner should be determined to use Duolingo as the first language learning source and meet the daily streak in the application. Moreover, the learner should commit to improving the foreign language they are learning for at least two hours a day.